2009
DOI: 10.1007/978-0-387-09597-4_10
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Cyclic Nucleotides: Their Roles in Junction Dynamics and Spermatogenesis

Abstract: Spermatogenesis is a highly complicated process in which functional spermatozoa (haploid, 1n) are generated from primitive mitotic spermatogonia (diploid, 2n). This process involves the differentiation and transformation of several types of germ cells as spermatocytes and spermatids undergo meiosis and differentiation. Due to its sophistication and complexity, testis possesses intrinsic mechanisms to modulate and regulate different stages of germ cell development under the intimate and indirect cooperation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 80 publications
0
21
0
1
Order By: Relevance
“…At sustained NO levels lower than 1 M NO actions are direct, for instance, NO can activate guanylate cyclase (GC) and MAP kinase signalling pathways. It is above 1 M NO that nitrosation of critical proteins such as poly ADP ribose polymerase and caspases involved in apoptosis occurs (Lee and Cheng 2008;Thomas et al 2008). In consonance with these concepts, a potential role for NO in the control of testicular function in health and disease is suggested.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…At sustained NO levels lower than 1 M NO actions are direct, for instance, NO can activate guanylate cyclase (GC) and MAP kinase signalling pathways. It is above 1 M NO that nitrosation of critical proteins such as poly ADP ribose polymerase and caspases involved in apoptosis occurs (Lee and Cheng 2008;Thomas et al 2008). In consonance with these concepts, a potential role for NO in the control of testicular function in health and disease is suggested.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, Lee and Cheng (2008) demonstrated that NOS/sGC/protein kinase G (PKG) participates in the regulation of the blood testis barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Both pathways are activated upon relaxin binding to Rxfp1, leading to the stimulated production of NO. Three major isoforms of Nos enzymes exist: endothelial Nos (Nos3) and neuronal Nos (Nos1), which are responsible for the continuous basal release of NO, and inducible Nos (Nos2), which is considered to be the more critical isoform, as its expression can be controlled by external factors [22]. NO is a small, diffusible, short-lived free radical gas active in diverse biological responses.…”
Section: Discussionmentioning
confidence: 99%
“…Each isoform has a reductase domain that contains a compound known as tetrahydrobiopterin (BH4), which is essential for efficient production of NO [24,25]. Interestingly, a testis-specific subclass of nNOS, known as TnNOS, has been recently identified as a major contributor to the formation of NO [31-34]. TnNOS is found to localize solely in the Leydig cells of the testis, thereby suggesting its involvement in steroidogenesis.…”
Section: Introductionmentioning
confidence: 99%